Evaluation of the condition of the eye surface in patients with burdened general somatic history. Early diagnosis, treatment and prevention methods - I. E. Shvailikova; E. I. Belikova (Офтальмохирургия, 2021)
Introduction. Modern computerisation, frequent use of contact correction, surgical interventions on the visual organ and long-term drug installations often lead to the formation and further progression of dry eye syndrome (DES) with subsequent increased sensitivity and inflammatory symptoms on the conjunctiva and cornea.Purpose. Evaluation of the condition of the eye surface in patients with a burdened general somatic history. Development of measures for prevention, diagnosis and comprehensive treatment of this condition.Material and methods. A retrospective analysis of disease histories and medical records of 108 patients (108 eyes) with phacoemulsification of uncomplicated cataract with IOL implantation was carried out. Patients were divided into three main groups based on the presence of burdening factors of somatic status and the course of the postoperative period: I group included patients with unburdened somatic status and no complications during the course of the postoperative period; II group included patients with burdened general somatic history with complications during the course of the postoperative period; III group included patients with burdened general somatic history with complications during the course of the postoperative period. III group of patients used a special scheme to prevent and treat inflammatory reactions from the eye surface.Results. I group patients were less likely to complain and had no clinical manifestations of conjunctival and corneal inflammatory responses. Accordingly, this group of patients did not require additional treatment, which is indicative of the low incidence of complications in this category of patients. II group patients who had been identified as predisposing factors for conjunctival and corneal inflammatory reactions and did not receive additional treatment were more likely to experience complaints and the frequency of clinical manifestations was 20% higher than III group patients. Patients in III group required additional treatment in the postoperative period.Conclusion. Prolonged prescription of high doses of drugs of different groups with different preservative and auxiliary substances content in patients after surgical intervention in some cases leads to damage to the conjunctival and corneal epithelium, which in turn causes an aggravation of symptoms of SSG with the development of inflammatory reaction of the conjunctiva and cornea. The application of preventive measures before and after the surgery leads to a significant reduction in the objective manifestations of the eye surface complications and, as a result, a reduction in the number of complaints from patients about discomfort in the postoperative period.